Broiler Chicken Meat Production Process Modeling at UD. Hari Ayam Using the Business Process Model and Notation (BPMN) Method - Elwino, Elwino Alif Ramadhan; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
Hari Ayam is a business that has been operating since 1988 and currently produces around 100–150 kilograms of chicken meat per day. The production process covers everything from processing to distribution to customers. However, the business faces several challenges, particularly the lack of clear and standardized documentation of its business processes. This issue makes it difficult to objectively assess performance or improve efficiency. In addition, the entire operation still relies heavily on the owner, resulting in a high workload and a lack of optimal task delegation. The absence of proper records related to transactions, production, income, and expenses further complicates the overall management of the business. This study aims to apply the Business Process Model and Notation (BPMN) method using the Bizagi application to map out the chicken meat production process at UD. Hari Ayam. The research focuses on the production and distribution stages and is limited to the design phase of the business process lifecycle. Through evaluation and simulation, the study is expected to provide a more efficient and structured view of the business processes. The results are intended to offer practical input for the business owner to improve workflow, enhance operational efficiency, and facilitate better oversight in support of the company’s future development.